Brucella hijacks host-mediated palmitoylation to stabilize and localize PrpA to the plasma membrane - Spera, Juan Manuel (2018)
Brucellaceae are a group of pathogenic intracellular bacteria with the ability to modulate the host response, both at the individual cell level and systemically. One of the hallmarks of the virulence process is the capacity of the bacteria to downregulate the adaptive and acquired host immune response through a plethora of virulence factors that directly impact several key signaling cascades. PrpA is one of those virulence factors that alters, via its polyclonal B-cell activity, the humoral and cellular immune responses of the host, ultimately favoring the establishment of a chronic infection. Even though PrpA affects B cells, it directly targets macrophages, triggering a response that ultimately affects B lymphocytes. In the present article we report that PrpA is S-palmitoylated in two N-terminal cysteine residues by the host cell and that this modification is necessary for its biological activity. Our results demonstrate that S-palmitoylation promotes PrpA migration to the host cell plasma membrane and stabilizes the protein during infection. These findings add a new mechanism exploited by this highly evolved pathogen to modulate the host immune response.